Peran UKM Dalam Meningkatkan Ketahanan Ekonomi Nasional - Tamara, Amelia Puspa (PT. Alahyan Publisher Sukabumi, 2023)
Training with the theme of the role of SMEs in improving national economic resilience is one solution to the problems faced by SMEs, namely the lack of understanding regarding the role and contribution of SMEs in increasing national economic resilience. The purpose of this activity is to increase the understanding of SMEs regarding the role of SMEs in increasing national economic resilience. The method of implementing this activity is training for SMEs of Potorono Tourism Village. The partner in this training activity is the Head of Potorono Tourism Village. The evaluation was carried out by giving questionnaires to trainees before and after delivering the material, and the result was that the comprehension ability of the participants increased by 42.5%.